Корекційно-виховна робота дітей молодшого шкільного віку із депривацією слуху засобами АФВ - Демчук, Світлана Петрівна; Базельчук, Наталія; Demchuk, Svitlana; Bazelchuk, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
Діти з депривацією слуху протягом дня не виконують фізіологічно необхідну кількість рухів, а нераціонально організовані фізкультурно-оздоровчі заходи не дають чинного ефекту в зміцненні здоров’я. Звідси очевидна необхідність наукового обґрунтування фізичного виховання дітей із депривацією слуху, розробки засобів, методів і форм організації корекційно-виховної роботи з ними. Мета – розкрити зміст і план корекційно-виховної роботи дітей молодшого шкільного віку з депривацією слуху засобами АФВ спеціальної школи-інтернату. Результати – розроблено зміст і план корекційно-виховної роботи дітей молодшого шкільного віку з депривацією слуху засобами АФВ. Висновки: зафіксовано позитивний вплив корекційно-виховної роботи дітей молодшого шкільного віку з депривацією слуху на покращення показників їхнього фізичного розвитку, підвищення рівня фізичної підготовленості, зміцнення здоров’я, соціальної адаптації. Ключові слова: корекція, молодший, депривація, слух, школяр. Children with hearing deprivation during the day don’t execute physiologically necessary number of moves, but not rationally organized physical cultural and health–improvement measures don’t provide functioning effect in health strengthening. It follows the necessity of scientific grounding of physical education of children with hearing deprivation, development of means, methods and forms of organization of correctional and educational work with them. Objective: To reveal the contents of the plan and correctional and educational work of primary school children with hearing deprivation by means of adaptive physical education of a special boarding school. Results: it was developed the content and plan of correctional and educational work of children of junior school age with hearing deprivation by means of adaptive physical education. Conclusions: it was recorded the positive influence of correctional and educational work of children of junior school age with hearing deprivation on improvement of indices of their physical development, increasing the level of physical preparedness, health strengthening, social adaptation.
Correctional and Educational work of Children of Junior School age with Hearing Deprivation by Means of Adaptive Physical Education
Keywords: корекція; молодший; депривація; слух; школяр; junior; deprivation; hearing; pupil; correction